Internationalising in small, incremental or larger steps? - Barkema, Harry G; Drogendijk, Rian (Journal of International Business Studies, 2007)
We argue that companies may enter foreign environments either incrementally, as suggested by long-established theory, or by taking larger steps that may result in lower initial performance but, through learning and experience, lead to increased performance in future expansions. This idea is corroborated by the experience of Dutch companies entering into Central and Eastern Europe. We also find that expansion steps may be too large, thereby limiting the exploration of foreign environments. Our study suggests that sequential internationalisation strategies do still matter, and that companies have to balance exploitation and exploration in internationalisation.